Analisis Tindak Tutur Mahasiswa Asal Papua di Universitas Syiah Kuala - Vicno Triwira Dhika; Ramli Ramli; Armia Armia (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
The research entitled “Analysis Speech Acts of Students from Papua at Syiah Kuala University” aims to describe the forms of speech acts of student from Papua at Syiah Kuala University, the method used in this research is descriptive qualitative. The data collection techniques used in this research were listening, engaging, dan note taking. From these data, classified according to the types of speech acts namely, direct speech acts, indirect speech acts, direct lateral speech acts, inlateral direct speech acts, lateral indirect speech acts, and inlateral indirect speech acts. Based of the data analysis, 56 speech acts were obtained, including 26 direct speech acts, 6 indirect speech acts, 7 direct lateral speech acts, 6 inlateral direct speech acts, 6 lateral indirect speech acts, and 5 indirect inlateral speech acts. From these data, there is a uniqueness in direct speech acts sentence. Speakers used “Toh” in the end of the sentence. There is a uniqueness in indirect speech acts sentence. Speakers used “toh” in the end of the sentence. Speakers used “Toh” to give information indirectly. There is a uniqueness in direct lateral speech acts sentece. Speakers used “Nunggu-nunggu”. There is a uniqueness in lateral indirect speech acts sentence. Speakers used “Eh” when they want to ask indirectly. There is uniqueness in indirect inlateral speech acts sentence. Speakers used “Wah” when they want to rejected the request.